Rentabilidad económica en la empresa eficacia Ecuador S.A. de la ciudad de Guayaquil durante el periodo 2022-2023. - Arauz Bustos, María Fernanda (2023)
The research on the economic profitability of Eficacia Ecuador S.A. during the period 2022-2023 focuses on the analysis of the accounting and financial management of the company, identifying inefficiencies in the cost structure that limit its net profitability. Through a thorough examination of the financial statements, significant findings were revealed that require optimization. The evaluation of key profitability indicators such as net margin and return on invested capital, showed that despite having a positive margin, it is below industry standards, suggesting that resources are not being used optimally. Based on these findings, financial optimization strategies were proposed, including cost reviews and the implementation of predictive analytics tools. These strategies are aligned with best practices in financial management and seek to improve the economic sustainability of the company. Ultimately, this research contributes to the understanding of the importance of efficient management of resources and costs in the competitive context of Guayaquil, laying the foundations for future research and practices in the accounting field.